2010
DOI: 10.1159/000320094
|View full text |Cite
|
Sign up to set email alerts
|

From Evidence to Rationale: Cardiovascular Protection by Angiotensin II Receptor Blockers Compared with Angiotensin-Converting Enzyme Inhibitors

Abstract: Clinical trials have shown the efficacy of angiotensin II receptor blockers (ARBs) in patients with hypertension and have suggested that ARBs are noninferior to angiotensin-converting enzyme (ACE) inhibitors in patients with ischemic heart disease and heart failure. The Heart Outcomes Prevention Evaluation (HOPE), a landmark study in high cardiovascular risk management, demonstrated the cardioprotection of the ACE inhibitor ramipril. Thus, in the recent Ongoing Telmisartan Alone and in Combination with Ramipri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 91 publications
2
8
0
Order By: Relevance
“…We must question also why the bodies that regulate the approval of antihypertensive drugs have not made BP measurement over 24 h mandatory for studies of drug efficacy and why the pharmaceutical industry funds such studies. Although 24-h ABPM is being used increasingly in clinical trials, it is surprising, nonetheless, that many studies continue to rely on clinic BP measurement to assess drug efficacy [3,[78][79][80][81][82][83][84][85][86][87]. Whereas these studies may be well conducted and may indeed show that the BP-lowering effect at one point in the 24-h profile is superior or inferior to another drug (or combination of drugs), they cannot provide information on the duration of BP-lowering efficacy of the drug being evaluated nor its effect on nocturnal phenomena, such as nondipping and the morning surge.…”
Section: Matinal Windowmentioning
confidence: 99%
“…We must question also why the bodies that regulate the approval of antihypertensive drugs have not made BP measurement over 24 h mandatory for studies of drug efficacy and why the pharmaceutical industry funds such studies. Although 24-h ABPM is being used increasingly in clinical trials, it is surprising, nonetheless, that many studies continue to rely on clinic BP measurement to assess drug efficacy [3,[78][79][80][81][82][83][84][85][86][87]. Whereas these studies may be well conducted and may indeed show that the BP-lowering effect at one point in the 24-h profile is superior or inferior to another drug (or combination of drugs), they cannot provide information on the duration of BP-lowering efficacy of the drug being evaluated nor its effect on nocturnal phenomena, such as nondipping and the morning surge.…”
Section: Matinal Windowmentioning
confidence: 99%
“…The current management for MI includes beta blockers, ACE inhibitors/ARBs, nitrates, and anti-thrombotic agents. Treatment with ACE inhibitors/ARBs or both in various clinical trials had not only ameliorated the disease status but also drastically improved the clinical outcome [4,5]. However, despite the improvement and availability of these therapies, the early mortality rate from acute MI is about 30%, with more than half of these deaths occurring before the stricken individual reaches the hospital [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, as demonstrated in large prospective double-blind, randomized clinical trial, valsartan has shown significant reduction in the incidence of diabetes and metabolic syndrome [10]. Unlike ACE inhibitors, valsartan does not exhibit dose limiting adverse effects such as persistent cough and angioedema [5].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Cardiology , Böhm et al [2] prepared a very comprehensive review and evaluation of the research data outlining the evidence supporting the proper usage of ACE-I agents in patients with complications, along with the available research on the proven benefits of ARB agents in similar patient groups.…”
mentioning
confidence: 99%
“…ON-TAR-GET, as described in excellent detail by Böhm et al [2] , was designed to flow from the pivotal HOPE study that demonstrated that ramipril 10 mg, when compared to placebo in high-risk patients, significantly reduced subsequent cardiac events [10] . The original intent of ON-TARGET was to add telmisartan 80 mg to ramipril 10 mg, with the expectation that this more comprehensive blockade of the RAAS system would further reduce cardiac events.…”
mentioning
confidence: 99%